Effect of sodium-glucose cotransporter 2 inhibitor in patients with non-alcoholic fatty liver disease and type 2 diabetes mellitus: a propensity score-matched analysis of real-world data. (March 2021) - Arai, Taeang; Atsukawa, Masanori; Tsubota, Akihito; Mikami, Shigeru; Ono, Hiroki; Kawano, Tadamichi; Yoshida, Yuji; Tanabe, Tomohide; Okubo, Tomomi; Hayama, Korenobu; Nakagawa-Iwashita, Ai; Itokawa, Norio; et al.
Background: Although sodium-glucose cotransporter 2 inhibitors (SGLT2-Is) improve not only glycemic control but also liver inflammation and fatty changes in patients with non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM), its sustainability and effect on liver fibrosis have remained unclear. The current study aimed to clarify the effects of 48-week SGLT2-I therapy on liver inflammation, fatty changes, and fibrosis in NAFLD patients with T2DM. Methods: This study evaluated the effects of SGLT2-I on NAFLD, including liver fibrosis assessed via transient elastography, in 56 patients with NAFLD who received SGLT2-I for 48 weeks. Moreover, changes in each clinical parameter between patients receiving SGLT2-I (the SGLT2-I group) and those receiving other oral hypoglycemic agents (OHAs) (the non-SGLT2-I group) were compared, using 1:1 propensity score matching to adjust for baseline factors. Results: The SGLT2-I group exhibited a significant decrease in controlled attenuation parameter (312 dB/m at baseline to 280 dB/m at week 48) and liver stiffness measurement (9.1–6.7 kPa) ( p < 0.001 for both). After propensity score matching (44 patients each in the SGLT2-I and non-SGLT2-I groups), no significant difference in HbA1c decrease was observed between the two groups. However, compared with the non-SGLT2-I group, the SGLT2-I group showed a significant decrease in body weight ( p < 0.001), alanine aminotransferase ( p = 0.02), uric acid ( p < 0.001), and Fibrosis-4 (FIB-4) index ( p = 0.01) at week 48. The improvement in FIB-4 index, defined as a ⩾10% decline from baseline at week 48, was 56.8% (25/44) in the SGLT2-I group and 20.5% (9/44) in the non-SGLT2-I group ( p < 0.001). Conclusion: SGLT2-Is improved not only glycemic control but also liver fatty infiltration and fibrosis in patients with NAFLD and T2DM, suggesting their possible superiority to other OHAs concerning these effects.